2020
DOI: 10.1021/acs.bioconjchem.0c00268
|View full text |Cite
|
Sign up to set email alerts
|

Investigational Therapies for Primary Hyperoxaluria

Abstract: Recent years have brought exciting new insights in the field of primary hyperoxaluria (PH), both on a basic research level as well as through the progress of novel therapeutics in clinical development. To date, very few supportive measures are available for patients suffering from PH, which, together with the severity of the disorder, make disease management challenging. Basic and clinical research and development efforts range from correcting the underlying gene mutations, preventing calcium oxalate crystal-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…While orthotopic liver transplantation is the only definitive cure for PH [ 50 ], numerous potential therapies for primary and enteric hyperoxalurias are currently being studied [ 69 ]. One approach to PH therapy involves downregulation of key enzymes, glycolate oxidase and lactate dehydrogenase, in the oxalate metabolism pathway through gene silencing methods [ 70 , 71 , 72 , 73 ] or enzyme inhibition [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While orthotopic liver transplantation is the only definitive cure for PH [ 50 ], numerous potential therapies for primary and enteric hyperoxalurias are currently being studied [ 69 ]. One approach to PH therapy involves downregulation of key enzymes, glycolate oxidase and lactate dehydrogenase, in the oxalate metabolism pathway through gene silencing methods [ 70 , 71 , 72 , 73 ] or enzyme inhibition [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…For enteric hyperoxaluria, oral administration of oxalate decarboxylase is currently being studied by two pharmaceutical companies with promising results [ 78 ] ( ). An in-depth review of novel investigational therapies for the hyperoxalurias was recently published by Kletzmayr et al [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Major progress has been made towards potential treatment of hyperoxaluric patients (Burns et al, 2020;Este `ve et al, 2019;Kletzmayr et al, 2020;Le Dudal et al, 2019;Liebow et al, 2017). These new molecules call for solid follow-up markers and surrogate endpoint (Milliner et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lumasiran reduces glycolate oxidase (GO) by degrading the mRNA-encoding GO (Figure 1 ). The reduction in GO results in a decline in liver-produced oxalates [ 4 , 5 ]. A double-blinded randomized trial in PH1 patients aged six years or older has demonstrated a 53.5% reduction in 24-hour urinary oxalate excretion and a substantial decrease in plasma oxalate levels [ 4 ].…”
Section: Introductionmentioning
confidence: 99%